Covid -19 : The Effects of Distance Learning in Indonesia based on a Commognitive Perspective - Adika Setyo Budi Lestari; Toto Nusantara; Susiswo; Tjang Daniel Chandra; Nonik Indrawatiningsih (Indian Journal of Forensic Medicine & Toxicology, 2021)
Distance learning is a learning system that does not take place in one room and there is no face-to-faceinteraction between the teacher and the learner. This study aims to determine the impact of implementingdistance learning in Indonesia from a commognitive point of view. This research is a descriptive type ofresearch with a total of 543 participants who come from high school students in Pasuruan district, Indonesia.Data collection using a questionnaire. After the questionnaire is collected, it is analyzed using the Milesand Huberman method through reduction, display data, and conclusion, then it will be studied based on thecommognitive theory. The results show that based on commognitive studies, students are more likely to stillneed a visual mediator as a visible object to be used as a communication medium, its realization dependson the material context. Students need to communicate to ask questions related to material that has not beenunderstood. So it can be said that visual mediator is important during distance learning.